Acute pancreatitis following adult liver transplantation: A systematic review - Danalıoğlu, Ahmet; JL. Mitchell, Oscar; K. Singh, Vikesh; Danalıoğlu, Ahmet Nasuh; Şentürk, Hakan; M. Cameron, Andrew; Gürakar, Ahmet (Turkish Journal of Gastroenterology, 2015)
Abstract Although uncommon, acute pancreatitis is a well-recognized, but generally serious, complication following liver transplantation. In addition to being more prevalent in patients who underwent liver transplantation than in the general population, it has a more aggressive course and can be responsible for significant morbidity and mortality. The post-liver transplant population has altered anatomy, increased comorbidities, and requires a myriad of drugs. These characteristics make them different from the pre-transplant population. Despite their retrospective nature, prior studies have identified numerous etiological factors that are associated with an increased risk of acute pancreatitis following liver transplantation. These can be broadly classified into the following four categories: surgical and anatomical factors, infections, post-transplant management, and post-transplant complications.The aim of this systematic review is to assimilate the available information regarding acute pancreatitis following adult liver transplantation to describe the risk factors and natural history of the disease and to highlight possible areas for further investigation.